Influence of risk factors on the long-term survival of oral rehabilitation with extra-narrow implants: a retrospective study (Journal of Applied Oral Science, 2022)
Objective: This study aimed to retrospectively collect clinical data to evaluate the influence of possible risk factors on the long-term success of implant treatment with extra-narrow (2.9 mm diameter) implants in a daily dental practice setting. Methodology: Data were collected from records of patients who received at least one extra-narrow implant from 2012 to 2017, regarding implant survival, prosthesis survival, patient characteristics, and implant characteristics. The association between the dependent variables “implant survival”, “prosthesis survival,” and “adverse events” related to patient and implant characteristics was statistically evaluated by chi-square tests. Moreover, implant and prosthesis survival were analyzed by Kaplan-Meier survival curves. Results: The sample was constituted of 58 patients (37 women and 21 men) with a mean age of 54.8 years old (SD: 12.5), followed up for up to eight years. In total, 86 extra-narrow implants were placed within this sample. Four implants were lost, resulting in an implant survival rate of 95.3%. A total of 55 prostheses were inserted and only one (1.8%) was lost, resulting in a prosthesis survival rate of 98.2%. The mean implant and prosthesis survival time was, respectively, 7.1 years and 6.3 years, according to the Kaplan-Meier survival analysis. A correlation was found between smoking and implant loss, which makes implant loss eight times more likely to occur in smokers than non-smokers. A significant association was also found between prosthesis loss and previous need of prosthesis repair. However, it was not considered clinically relevant. No association was found between the occurrence of adverse events and later implant or prosthesis loss. Conclusion: High implant and prosthesis survival rates were found in the long term for treatment with extra-narrow implants. Moreover, a significant correlation between smoking and implant loss was observed.